A rapid national survey of terrestrial and semi-aquatic mammals using environmental DNA metabarcoding - Holly A. Broadhurst; Elin E. Smith; Jake M. Jackman; Robert Raynor; Claire Howe; Naiara Guimarães Sales; Allan D. McDevitt (Mammalian Biology, 2026)
Assessing the distribution and diversity of terrestrial and semi-aquatic mammals is fundamental for effective conservation efforts. Environmental DNA (eDNA) metabarcoding has emerged as a rapid and cost-effective method for surveying mammals. It has promising avenues for conducting national surveys and enabling comprehensive assessments of mammalian populations across diverse habitats. We collected eDNA samples from 60 water systems across six regions in England (from north to south), United Kingdom, over a period of up to four days in each region. We detected 26 mammals from five taxonomic orders across all sampling locations, recovering 53–89% of the known mammal community in each region. Our findings underscore the feasibility of utilising eDNA metabarcoding for rapidly surveying mammal populations on a national scale, potentially complementing data from existing surveys/records or implementing in data deficient regions. However, challenges remain for surveying certain species using this method, with varying levels of detectability of key species (e.g. otters) across regions.

Alignment between Duplex Sequencing and transgenic rodent mutation assay data in the assessment of in vivo NDMA-induced mutagenesis - Anne L. Ashford; Daniela Nachmanson; John W. Wills; Jacob E. Higgins; Thomas H. Smith; Kevin C. Vavra; Farah A. Dahalan; Jonathan Howe; Joanne M. Elloway; Jesse J. Salk; Ann Doherty; Anthony M. Lynch (Archives of Toxicology, 2025)

The frequency and chemical phenotype of neighboring plants determine the effects of intraspecific plant diversity - Andrea E. Glassmire; Kayleigh C. Hauri; Daniel B. Turner; Luke N. Zehr; Koichi Sugimoto; Gregg A. Howe; William C. Wetzel (Ecology, 2024)
Associational effects, whereby plants influence the biotic interactions of their neighbors, are an important component of plant–insect interactions. Plant chemistry has been hypothesized to mediate these interactions. The role of chemistry in associational effects, however, has been unclear in part because the diversity of plant chemistry makes it difficult to tease apart the importance and roles of particular classes of compounds. We examined the chemical ecology of associational effects using backcross‐bred plants of the Solanum pennellii introgression lines. We used eight genotypes from the introgression line system to establish 14 unique neighborhood treatments that maximized differences in acyl sugars, proteinase inhibitor, and terpene chemical diversity. We found that the chemical traits of the neighboring plant, rather than simply the number of introgression lines within a neighborhood, influenced insect abundance on focal plants. Furthermore, within‐chemical class diversity had contrasting effects on herbivore and predator abundances, and depended on the frequency of neighboring plant chemotypes. Notably, we found insect mobility—flying versus crawling—played a key role in insect response to phytochemistry. We highlight that the frequency and chemical phenotype of plant neighbors underlie associational effects and suggest this may be an important mechanism in maintaining intraspecific phytochemical variation within plant populations.

Association of diet with per- and polyfluoroalkyl substances in plasma and human milk in the New Hampshire Birth Cohort Study - Yuting Wang; Jiang Gui; Caitlin G. Howe; Jennifer A. Emond; Rachel L. Criswell; Lisa G. Gallagher; Carin A. Huset; Lisa A. Peterson; Julianne Cook Botelho; Antonia M. Calafat; Brock Christensen; Margaret R. Karagas; et al. (Science of The Total Environment, 2024)

Quantification and classification of a giant fluvial-distributive system - the Triassic Mungaroo Formation, NWS, Australia - T.H.D. Payenberg; B.J. Willis; P. Sixsmith; S.D. Connell; A. Powell; K.T. Milliken; H.W. Posamentier; A. Allgoewer; E. Meyers; T. Marsh; M.D. Sullivan; S.C. Lang; et al. (Earth-Science Reviews, 2024)

Periconceptional and Prenatal Exposure to Metals and Extracellular Vesicle and Particle miRNAs in Human Milk: A Pilot Study - Caitlin G. Howe; David A. Armstrong; Meghan E. Muse; Diane Gilbert-Diamond; Jiang Gui; Anne G. Hoen; Thomas J. Palys; Roxanna L. Barnaby; Bruce A. Stanton; Brian P. Jackson; Brock C. Christensen; Margaret R. Karagas (Exposure and Health, 2023)

Associations between area-level arsenic exposure and adverse birth outcomes: An Echo-wide cohort analysis - Jonathan V. Lewis; Emily A. Knapp; Shivani Bakre; Aisha S. Dickerson; Theresa M. Bastain; Casper Bendixsen; Deborah H. Bennett; Carlos A. Camargo; Andrea E. Cassidy-Bushrow; Elena Colicino; Viren D’Sa; Dana Dabelea; et al. (Environmental Research, 2023)

How can diverse national food and land-use priorities be reconciled with global sustainability targets? Lessons from the FABLE initiative - Aline Mosnier; Guido Schmidt-Traub; Michael Obersteiner; Sarah Jones; Valeria Javalera-Rincon; Fabrice DeClerck; Marcus Thomson; Frank Sperling; Paula Harrison; Katya Pérez-Guzmán; Gordon Carlos McCord; Javier Navarro-Garcia; et al. (Sustainability Science, 2023)
There is an urgent need for countries to transition their national food and land-use systems toward food and nutritional security, climate stability, and environmental integrity. How can countries satisfy their demands while jointly delivering the required transformative change to achieve global sustainability targets? Here, we present a collaborative approach developed with the FABLE—Food, Agriculture, Biodiversity, Land, and Energy—Consortium to reconcile both global and national elements for developing national food and land-use system pathways. This approach includes three key features: (1) global targets, (2) country-driven multi-objective pathways, and (3) multiple iterations of pathway refinement informed by both national and international impacts. This approach strengthens policy coherence and highlights where greater national and international ambition is needed to achieve global goals (e.g., the SDGs). We discuss how this could be used to support future climate and biodiversity negotiations and what further developments would be needed.

Adenosine A2A receptor in schizophrenia: an in vivo brain PET imaging study - Tiago Reis Marques; Sridhar Natesan; Eugenii A. Rabiner; Graham E. Searle; Roger Gunn; Oliver D. Howes; Shitij Kapur (Psychopharmacology, 2022)
Adenosine A 2A receptors are highly enriched in the basal ganglia system, a region that is functionally implicated in schizophrenia. Preclinical evidence suggests a cross-regulation between adenosine A 2A and dopamine D 2 receptors in this region and that it is linked to the sensitization of the dopamine system. However, the relationship between A 2A receptor availability and schizophrenia has not been directly examined in vivo in patients with this disorder. To investigate, using positron emission tomography (PET), the availability of A 2A receptors in patients diagnosed with schizophrenia in comparison to matched healthy controls. A 2A receptor availability was measured using the PET tracer [ 11 C]SCH442416. Twelve male patients with chronic schizophrenia were compared to 13 matched healthy subjects. All patients were medicated with antipsychotics and none presented with any motor or extrapyramidal symptoms. Binding potential (BP ND ), a ratio measure between specific and non-specific tracer uptake, were compared between the groups for the caudate, putamen, accumbens and globus pallidum. There was no differences between A 2A receptor binding potential (BP ND ) of schizophrenia patients in the caudate ( p = 0.16), putamen ( p = 0.86), accumbens ( p = 0.44) and globus pallidum ( p = 0.09) to that of matched healthy subjects. There was also no significant correlation between [11C]SCH442416 binding and severity of psychotic symptoms ( p = 0.2 to 0.82) or antipsychotic dosage ( p = 0.13 to 0.34). By showing that A2A receptor availability in medicated patients with chronic male schizophrenia is not different than in healthy controls, this study does not support the primary role of this receptor in the pathogenesis of schizophrenia.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Palmitic Acid and Oleic Acid Differently Modulate TLR2-Mediated Inflammatory Responses in Microglia and Macrophages - Anne-Marie Howe; Sinéad Burke; Marcella E. O’Reilly; Fiona C. McGillicuddy; Derek A. Costello (Molecular Neurobiology, 2022)
The relationship between systemic immunity and neuroinflammation is widely recognised. Infiltration of peripheral immune cells to the CNS during certain chronic inflammatory states contributes significantly to neuropathology. Obesity and its co-morbidities are primary risk factors for neuroinflammatory and neurodegenerative conditions, including Alzheimer’s disease (AD). Dietary fats are among the most proinflammatory components of the obesogenic diet and play a prominent role in the low-grade systemic inflammation associated with the obese state. Saturated fatty acid (SFA) is largely implicated in the negative consequences of obesity, while the health benefits of monounsaturated fatty acid (MUFA) are widely acknowledged. The current study sought to explore whether SFA and MUFA differently modulate inflammatory responses in the brain, compared with peripheral immune cells. Moreover, we assessed the neuroinflammatory impact of high-fat-induced obesity and hypothesised that a MUFA-rich diet might mitigate inflammation despite obesogenic conditions. Toll-like receptor (TLR)2 mediates the inflammation associated with both obesity and AD. Using the TLR2 agonist lipoteichoic acid (LTA), we report that pre-exposure to either palmitic acid (PA) or oleic acid (OA) attenuated cytokine secretion from microglia, but heightened sensitivity to nitric oxide (NO) production. The reduction in cytokine secretion was mirrored in LTA-stimulated macrophages following exposure to PA only, while effects on NO were restricted to OA, highlighting important cell-specific differences. An obesogenic diet over 12 weeks did not induce prominent inflammatory changes in either cortex or hippocampus, irrespective of fat composition. However, we reveal a clear disparity in the effects of MUFA under obesogenic and non-obesogenic conditions.

Nitrate enrichment has lineage specific effects on Pocillopora acuta adults, but no transgenerational effects in planulae - Marie E. Strader; Lauren I. Howe-Kerr; Jordan A. Sims; Kelly E. Speare; Amanda N. Shore; Deron E. Burkepile; Adrienne M. S. Correa (Coral Reefs, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Impacts of zebra mussels (Dreissena polymorpha) on isotopic niche size and niche overlap among fish species in a mesotrophic lake - Alexandra L. Morrison; Mary A. Thelen; Sarah E. Howe; Kyle D. Zimmer; Brian R. Herwig; David F. Staples; Margaret C. McEachran (Biological Invasions, 2021)

Expanding coral reproductive knowledge using remotely operated vehicles (ROV): broadcast-spawning observations of mesophotic corals at the Flower Garden Banks - Marie E. Strader; Hannah E. Aichelman; Carlos A. Tramonte; Hayden E. W. Dickerson; Brooke E. Benson; Lauren I. Howe-Kerr; Emma L. Hickerson; Sarah W. Davies (Marine Biodiversity, 2021)

Corrigendum: On a Reef Far, Far Away: Anthropogenic Impacts Following Extreme Storms Affect Sponge Health and Bacterial Communities - Amanda Shore; Jordan A. Sims; Michael Grimes; Lauren I. Howe-Kerr; Carsten G. B. Grupstra; Shawn M. Doyle; Lauren Stadler; Jason B. Sylvan; Kathryn E. F. Shamberger; Sarah W. Davies; Lory Z. Santiago-Vázquez; Adrienne M. S. Correa (Frontiers in Marine Science, 2021)

On a Reef Far, Far Away: Anthropogenic Impacts Following Extreme Storms Affect Sponge Health and Bacterial Communities - Amanda Shore; Jordan A. Sims; Michael Grimes; Lauren I. Howe-Kerr; Carsten G. B. Grupstra; Shawn M. Doyle; Lauren Stadler; Jason B. Sylvan; Kathryn E. F. Shamberger; Sarah W. Davies; Lory Z. Santiago-Vázquez; Adrienne M. S. Correa (Frontiers in Marine Science, 2021)
Terrestrial runoff can negatively impact marine ecosystems through stressors including excess nutrients, freshwater, sediments, and contaminants. Severe storms, which are increasing with global climate change, generate massive inputs of runoff over short timescales (hours to days); such runoff impacted offshore reefs in the northwest Gulf of Mexico (NW GoM) following severe storms in 2016 and 2017. Several weeks after coastal flooding from these events, NW GoM reef corals, sponges, and other benthic invertebrates ∼185 km offshore experienced mortality (2016 only) and/or sub-lethal stress (both years). To assess the impact of storm-derived runoff on reef filter feeders, we characterized the bacterial communities of two sponges, Agelas clathrodes and Xestospongia muta , from offshore reefs during periods of sub-lethal stress and no stress over a three-year period (2016—2018). Sponge-associated and seawater-associated bacterial communities were altered during both flood years. Additionally, we found evidence of wastewater contamination (based on 16S rRNA gene libraries and quantitative PCR) in offshore sponge samples, but not in seawater samples, following these flood years. Signs of wastewater contamination were absent during the no-flood year. We show that flood events from severe storms have the capacity to reach offshore reef ecosystems and impact resident benthic organisms. Such impacts are most readily detected if baseline data on organismal physiology and associated microbiome composition are available. This highlights the need for molecular and microbial time series of benthic organisms in near- and offshore reef ecosystems, and the continued mitigation of stormwater runoff and climate change impacts.

Regional differences in aspen (Populus tremuloides Michx.) seedling response to an established nursery protocol - Alexander A. Howe; Simon M. Landhäusser; Owen T. Burney; James N. Long; Karen E. Mock (New Forests, 2020)

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Direct Measurements of Bed Shear Stress under Swash Flows on Steep Laboratory Slopes at Medium to Prototype Scales - Daniel Howe; Chris E. Blenkinsopp; Ian L. Turner; Tom E. Baldock; Jack A. Puleo (Journal of Marine Science and Engineering, 2019)
Robust measurements of bed shear stress under wave runup flows are necessary to inform beachface sediment transport modelling. In this study, direct measurements of swash zone bed shear stress were obtained in medium and prototype-scale laboratory experiments on steep slopes. Peak shear stresses coincided with the arrival of uprush swash fronts and high-resolution measurement of swash surface profiles indicated a consistently seaward sloping swash surface with minimal evidence of a landward sloping swash front. The quadratic stress law was applied to back-calculate time-varying friction factors, which were observed to decrease with increasing Reynolds number on smooth slopes, consistent with theory for steady flows. Additionally, friction factors remained relatively constant throughout the swash cycle (except around flow reversal), with a variation of approximately ±20% from the mean value and with only small differences between uprush and backwash. Measured friction factors were observed to be larger than expected when plotted on the Moody or wave friction diagram for a given Reynolds number and relative roughness, consistent with previous field and laboratory studies at various scales.

Transforming growth factor-β promotes basement membrane fibrosis, alters perivascular cerebrospinal fluid distribution, and worsens neurological recovery in the aged brain after stroke - Matthew D. Howe; J. Weldon Furr; Yashasvee Munshi; Meaghan A. Roy-O’Reilly; Michael E. Maniskas; Edward C. Koellhoffer; John d’Aigle; Lauren H. Sansing; Louise D. McCullough; Akihiko Urayama (GeroScience, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Influences of Natural and Anthropogenic Factors and Tidal Restoration on Terrestrial Arthropod Assemblages in West Coast North American Estuarine Wetlands - Aaron T. David; Pascale A. L. Goertler; Stuart H. Munsch; Brittany R. Jones; Charles A. Simenstad; Jason D. Toft; Jeffery R. Cordell; Emily R. Howe; Ayesha Gray; Michael P. Hannam; William Matsubu; Erin E. Morgan (Estuaries and Coasts, 2016)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Do estuaries pose a toxic contamination risk for wading birds? - J. T. Smith; L. A. Walker; R. F. Shore; S. E. A. le V. dit Durell; P. D. Howe; M. Taylor (Ecotoxicology, 2009)

Cigarette smoking, body mass index, gastro-esophageal reflux disease, and non-steroidal anti-inflammatory drug use and risk of subtypes of esophageal and gastric cancers by P53 overexpression - Jonine D. Figueroa; Mary Beth Terry; Marilie D. Gammon; Thomas L. Vaughan; Harvey A. Risch; Fang-Fang Zhang; David E. Kleiner; William P. Bennett; Christine L. Howe; Robert Dubrow; Susan T. Mayne; Joseph F. Fraumeni; et al. (Cancer Causes & Control, 2009)

How spatially coherent and statistically robust are temporal changes in extreme precipitation in the contiguous USA? - S. C. Pryor; J. A. Howe; K. E. Kunkel (International Journal of Climatology, 2009)
Century‐long precipitation records from stations in the contiguous USA indicate an increased frequency of rainy days over the past century and some evolution in the probability distributions of precipitation amount. Temporal trends in eight metrics of the precipitation climate are of similar magnitude and sign regardless of whether they are derived from bootstrapping of regression residuals or using the Kendall's tau statistic, though the bootstrap technique generally resolved a larger number of ‘significant’ trends. There is substantial variability in terms of the magnitude, significance and sign of the linear trends with specific metrics, and they are sensitive to recording bias of light precipitation events in the early part of the 20th century. The majority of stations that exhibit significant linear trends show evidence of increases in the intensity of events above the 95th percentile. The resolved trends tend to have a larger magnitude at the end of the century. Spatial variability as manifest in the spatial autocorrelation in the interannual variability and trends in extreme metrics is manifest at a range of scales, but in general the correlation between stations is significant only for separation of distances of a few tens of kilometres. The largest trends towards increased annual total precipitation, number of rainy days and intense precipitation (e.g. fraction of precipitation derived from events in excess of the 90th percentile value) are focussed on the Central Plains/northwestern Midwest. Copyright © 2008 Royal Meteorological Society

Integrated Measures of Anthropogenic Stress in the U.S. Great Lakes Basin - Nicholas P. Danz; Gerald J. Niemi; Ronald R. Regal; Tom Hollenhorst; Lucinda B. Johnson; JoAnn M. Hanowski; Richard P. Axler; Jan J. H. Ciborowski; Thomas Hrabik; Valerie J. Brady; John R. Kelly; John A. Morrice; et al. (Environmental Management, 2007)

Dietary fiber intake and ovarian cancer risk: a prospective cohort study - Stephanie A. N. Silvera; Meera Jain; Geoffrey R. Howe; Anthony B. Miller; Thomas E. Rohan (Cancer Causes & Control, 2007)

Growth Suppression of Canola Through Wheat Stubble I. Separating Physical and Biochemical Causes in the Field - S. E. Bruce; J. A. Kirkegaard; J. Pratley; G. Howe (Plant and Soil, 2006)

Glycemic index, glycemic load, and pancreatic cancer risk (Canada) - Stephanie A. N. Silvera; Thomas E. Rohan; Meera Jain; Paul D. Terry; Geoffrey R. Howe; Anthony B. Miller (Cancer Causes & Control, 2005)

Highly variable SSR markers in Douglas-fir: Mendelian inheritance and map locations - G. T. Slavov; G. T. Howe; I. Yakovlev; K. J. Edwards; K. V. Krutovskii; G. A. Tuskan; J. E. Carlson; S. H. Strauss; W. T. Adams (Theoretical and Applied Genetics, 2004)

Non-dietary factors as risk factors for breast cancer, and as effect modifiers of the association of fat intake and risk of breast cancer - David J. Hunter; Donna Spiegelman; Hans-Olov Adami; Piet A. van den Brandt; Aaron R. Folsom; R. Alexandra Goldbohm; Saxon Graham; Goeffrey R. Howe; Lawrence H. Kushi; James R. Marshall; Anthony B. Miller; Frank E. Speizer; et al. (Cancer Causes & Control, 1997)

Biological components of Sites of Special Scientific Interest in Wales - T. H. Blackstock; D. P. Stevens; E. A. Howe (Biodiversity and Conservation, 1996)

A recombinant fowlpox virus that expresses the VP2 antigen of infectious bursal disease virus induces protection against mortality caused by the virus - C. D. Bayliss; R. W. Peters; Jane K. A. Cook; R. L. Reece; K. Howes; M. M. Binns; M. E. G. Boursnell (Archives of Virology, 1991)

Growth studies of parainfluenza virus (type 2) - C. Howe; S. A. Milliken; E. W. Newcomb (Archives of Virology, 1970)